Examining the Relationship between Corporate Social Responsibility Practices and Firm Reputation in the Financial Services Sector in Brazil - Miguel, Leandro (International Journal of Strategic Management, 2023)
Purpose: The aim of the study was to Examine the Relationship between Corporate Social Responsibility Practices and Firm Reputation in the Financial Services Sector in Brazil Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The study examining the relationship between Corporate Social Responsibility (CSR) practices and firm reputation in the financial services sector in Brazil found a strong positive correlation between the two variables. Financial firms that actively engaged in CSR initiatives were observed to have significantly enhanced their reputation among stakeholders, including customers, investors, and the public. This positive reputation was attributed to the perception of ethical and socially responsible behavior, ultimately leading to increased trust and loyalty from clients and improved financial performance for the firms involved in CSR activities. Unique Contribution to Theory, Practice and Policy: The stakeholder theory, legitimacy theory and legitimacy theory may be used to anchor future studies on the examining the relationship between corporate social responsibility practices and firm reputation in the financial services sector in Brazil. Regular, detailed, and standardized reporting on CSR initiatives can improve stakeholder trust and help investors make informed decisions. Collaborate with regulators and industry associations to establish a comprehensive regulatory framework for CSR practices in the financial services sector.